Design of CEFR-Based Arabic Language Proficiency Test Indicators In The Arabic Language Education Department - Nurdianto, Talqis; Hidayat, Yayat; Fitrianto, Ibnu Ali Abdullah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This research aims to establish test indicators corresponding to CEFR-based Arabic language proficiency levels, especially for beginner levels (A1 and A2). This research uses content analysis methods to develop CEFR-based Arabic language proficiency test indicators. This research was also carried out by reviewing several sources, including the CEFR framework and several previous studies on the design of Arabic language proficiency tests. The CEFR-based Arabic language proficiency test indicators were created by considering descriptions of Arabic grammatical competence in nahwu (syntaxis), sharf (morphological), balaghah (rhetoric) science, and ‘ilm dilalah (semantics). The design of CEFR-based Arabic language proficiency test indicators can help overcome difficulties in measuring Arabic language proficiency for students in Indonesia. Using the CEFR framework, this research offers an alternative solution for developing a curriculum and test design appropriate to the level of Arabic language proficiency. This research concludes that the design of CEFR-based Arabic language proficiency test indicators can help improve the quality of Arabic language learning and ensure that students have abilities that comply with international standards.